(untitled) (International Journal of Engineering and Computer Science, 2014)
Due to many advance technology Internet of things is now used in many application including low-cost sensors, low-power processors, commerce, industry, and education applications. Interconnection can be done with other object around us with the other world through Internet of thing (IoT) which are virtual connection, even wireless connectivity are available. In this paper, we take you to the introduction of Internet of things (IOT), different applications and architectures of Internet of things.